Technical and tactical discriminatory factors between winners and defeated elite karate athletes - Tabben, M.; Conte, D.; Haddad, M.; Chamari, K. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To assess the technical and tactical demands of elite karate athletes in relation to 3 match sequences (ie, advantage, disadvantage, and drawing) and match outcome (ie, win/defeat). Methods: One hundred twenty elite seniors' (60 men and 60 women) World Karate Federation combats were analyzed during 2 World Championships (2012 and 2014). Specific karate attributes (strategy, technique, tactic, target, and effectiveness) were evaluated and classified into 3 sequences: advantage, disadvantage, and drawing. Results: Karatekas performed more combination techniques in disadvantage sequences than in drawing sequences (P = .011). A higher number of timed-attack actions were reported during advantage sequences than during drawing sequences (P = .048). Winners of the whole combat had higher lower-limb technique rate (1.0 [0.9] vs 0.1 [0.3]; P = .044) and less rate of timed attack (0.3 [0.5] vs 0.6 [1.0]; P = .030) than defeated karatekas during advantage and drawing sequences, respectively. Conclusions: Winners used higher lower-limb technique and less timed-attack rates than defeated karatekas in advantage and drawing sequences, respectively. Indeed, using lower-limb technique during advantageous situations could be a powerful strategy to increase the lead. Therefore, it seems fundamental for coaches of top elite karatekas to put their athletes in simulated situations and push them to increase their use of lower-limb techniques.